James Madison and the struggle for the Bill of Rights - Labunski, Richard E. (Pivotal moments in American history., 2006)
Today we hold the Constitution in such high regard that we can hardly imagine how hotly contested was its adoption. In fact, many of the thirteen states saw fierce debate over the document, and ratification was by no means certain. Virginia, the largest and most influential state, approved the Constitution by the barest of margins, and only after an epic political battle between James Madison and Patrick Henry. Now Richard Labunski offers a dramatic account of a time when the entire American experiment hung in the balance, only to be saved by the most unlikely of heroes--the diminutive and exc.